设f(x)是定义在R上的增函数,令g(x)=f(x)-f(2010-x).(1)求证:g(x)+g(2010-x)为定值

1个回答

  • (1)证明:∵g(x)=f(x)-f(2010-x)

    ∴g(2010-x)=f(2010-x)-f(x)

    ∴g(x)+g(2010-x)=[f(x)-f(2010-x)]+[f(2010-x)-f(x)]=0

    ∴为定值0,得证:

    (2)设x1<x2

    g(x1)=f(x1)-f(2010-x1)

    g(x2)=f(x2)-f(2010-x2)

    ∴g(x1)-g(x2)=[f(x1)-f(x2)]+[f(2010-x2)-f(2010-x1)]

    ∵f(x)在R上增函数,∴f(x1)-f(x2)<0;

    又x1<x2,-x1>-x2,2010-x1>2010-x2

    ∴f(2010-x1)>f(2010-x2)

    ∴f(2010-x2)-f(2010-x1)<0

    ∴[f(x1)-f(x2)]+[f(2010-x2)-f(2010-x1)]<0

    ∴g(x1)-g(x2)<0

    ∴g(x1)<g(x2)

    g(x)在R上是增函数;